Investigation on secondary deformation of ultrafine SiC particles reinforced LM25 metal matrix composites. (2021) - Kanu, Nand Jee; Mangalam, Amogh; Gupta, Eva; Vates, Umesh Kumar; Singh, Gyanendra Kumar; Sinha, Devendra Kumar
Abstract: In the past few years, aluminum alloys have been widely used in the field of automation, aeronautical, and heavy industries due to their light weight, high specific strength, high corrosion resistance, and excellent formability. However, the properties related to microstructure and dispersed medium are constant throughout the past research. The present research work is focused on the tensile tests of LM25 (reinforced with 10% SiC) metal matrix composites (MMCs) for its applications in aerospace industry through ultrasonic treatment (UST) of the liquid melt by varying the ultrasonic sonotrode (US) power and ultrasonic frequency. The high intensity UST is carried out on the LM25 MMCs reinforced with 10% SiC (proportion by weight) in a temperature range between 850 and 750 °C. The preheated mold at 250 °C temperature is used to cast the liquid melt after the UST. The castings are produced by varying time intervals and temperature ranges at distinct US power levels such as (a) 65% and (b) 75%. The casting process samples are prepared as per ASTM standard for tensile tests to reveal the effects of the UST. In the present investigation, the effects of UST on melt temperature, processing time, US power, and ultrasonic frequency (kHz) are studied in detail.